2017
DOI: 10.1140/epjc/s10052-017-5376-6
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational lensing by a Horndeski black hole

Abstract: In this article we study gravitational lensing by non-rotating and asymptotically flat black holes in Horndeski theory. By adopting the strong deflection limit, we calculate the deflection angle, from which we obtain the positions and the magnifications of the relativistic images. We compare our results with those corresponding to black holes in General Relativity. We analyze the astrophysical consequences in the case of the nearest supermassive black holes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 67 publications
0
21
2
Order By: Relevance
“…The observations that follow from the Horndeski theory and its mathematical implications include determining observables such as angular positions, separation, magnification and fluxes: a case study of astrophysical applications for Sagittarius A* and M87 can be found in [11]. Additionally, distinct researches include linear Horndeski theories to study dark energy and gravitational waves [83], and Horndeski gravity to study dark matter [84].…”
Section: Discussionmentioning
confidence: 99%
“…The observations that follow from the Horndeski theory and its mathematical implications include determining observables such as angular positions, separation, magnification and fluxes: a case study of astrophysical applications for Sagittarius A* and M87 can be found in [11]. Additionally, distinct researches include linear Horndeski theories to study dark energy and gravitational waves [83], and Horndeski gravity to study dark matter [84].…”
Section: Discussionmentioning
confidence: 99%
“…Note that the solution (16) with α = q = 0 reduces to deflection angle of Schwarzcshild BH in the leading order terms. Moreover, it can be seen that the α parameter increases the deflection angle.…”
Section: Deflection Angle Of Einstein-non-linear Maxwell-yukawa mentioning
confidence: 99%
“…The field equations resulting from Eq. (9) admit a static, spherically symmetric, and asymptotically flat solution of the form [95]…”
Section: Evaluation Of Photon Lensing For Horndeski Black Holesmentioning
confidence: 99%